Evaluation of a Single PCR Assays on Cp5 Gene for Differentiation of Entamoeba histolytica and E. dispar - S Rostamighalehjaghi; R Jamali; S Rezaie; Z Babaei; H Hooshyar; M Rezaeian (Tehran University of Medical Sciences, 2010)
Background: We examined a molecular method with a single-PCR for amplification of a part of CP5 gene enabling us to differentiate the pathogenic species, Entamoeba histolytica, from the non-pathogenic species, E. dispar. Methods: We developed a single PCR method for this purpose.  After investigation of GenBank, primer pairs were designed from highly conserved regions of cysteine proteinase (CP5) gene. The primers were utilized in PCR using isolated genomic DNA template of E. histolytica and the PCR products were then sequenced. The same primer and method for PCR was used for isolated genomic DNA template of E. dispar. Results: A fragment of about 950 bp was isolated in PCR by using DNA from E. histolytica, however, no banding pattern was produced by using the same primers for E. dispar. We characterized CP5 gene at molecular level in E. histolytica isolates from 22 positive; including 20 non-dysentery samples isolated from both cities as well as two dysentery samples isolated only from Tabriz. Nucleotide sequence comparison in gene data banks (NCBI, NIH) revealed significant homology with CP5 gene in E. histolytica isolates Conclusion: We developed a PCR method, which could detect simply and rapidly E. histolytica by amplifying a specific PCR fragment.